Emerging Solar Energy Materials - Ameen, Sadia; Shaheer Akhtar, M.; Shin, Hyung-Shik (IntechOpen, 2018)
This book provides the fundamental understanding of the functioning of solar cellsand the materials for the effective utilization of energy resources. The main objective of writing this book is to create a comprehensive and easy-to-understand source of information on the advances in the rapidly growing research on solar cells. Emerging Solar Energy Materials comprises 12 chapters written by the experts in the solar cell field and is organized with the intention to provide a big picture of the latest progress in the solar cell field and at the same time give an in-depth discussion on fundamentals of solar cells for interested audiences. In this book, each part opens with a new author's essay highlighting their work for contribution toward solar energy. Critical, cutting-edge subjects are addressed, including: Photovoltaic device technology and energy applications; Functional solar energy materials; New concept in solar energy; Perovskite solar cells; Dye-sensitized solar cells; Organic solar cells; Thin-film solar cells. The book is written for a large and broad readership including researchers and university graduate students from diverse backgrounds such as chemistry, physics, materials science, and photovoltaic device technology. The book includes enough information on the basics to be used as a textbook undergraduate coursework in engineering and the sciences.